PECULIARITIES OF NEUROLOGICAL AND NEUROPSYCHOLOGICAL SEMIOTICS IN PATIENTS WITH CHRONIC RENAL INSUFFICIENCY IN PROGRAM HEMODIALYSIS - Delva І.І. (World of Medicine and Biology, 2013)
Neurological disorders are majors determinants of life quality in patients with chronic renal insufficiency who are treated with program hemodialysis. The aim of the study was to establish regularities in neurological status changes, dynamics and nature of cognitive, emotional and sleep disorders in patients with chronic renal insufficiency depending on length of program hemodialysis treatment. The study included 44 patients with chronic renal insufficiency who have different experience of program hemodialysis from 1 year till 10 years. The control group consisted of 15 conditionally healthy persons. It had been found that neurological complications in such patients have in their development certain evolution, in form of primary emotional disorders, followed by the formation of pyramidal syndrome, extrapyramidal, atactic disorders and mild cognitive impairments.